Monitoreo de las posibilidades de recursos solares y eólicos en el cantón Zapotillo de la provincia de Loja. Caso práctico en destilador solar. - Buri Quizhpe, Luis Alfredo (2010)
The present research work “MONITOR THE POSIBILITIES OF THE SOLAR AND EOLITHICS RESOURSES IN ZAPOTILLO CANTON OF LOJA PROVINCE. A PRACTICAL CASE IN SOLAR FILTER” it was obtained information, which is distributed in four chapters. The first chapter refers to the basis from the solar and Eolithic energy, its generalities, applications advantages and disadvantages. In the second chapter it is describes elaborated a mathematical model for the solar radiation calculus. The third one collects information about a meteorological station, its needs, the description of different elements which compose it, moreover it is presented on weekly and monthly reports about the study done, and the obtained results. The last chapter is assigned to the solar filter, its functioning, the calculus of different termical magnitudes, productivity results and daily and monthly efficiency, the same as the microbiological analysis of the water samples of the Catamayo river and the filter one.